Advances in pediatric medical imaging: A review of radiation exposure reduction techniques - Aloufi, Sami Mohammed (International journal of health sciences, 2022)
Medical imaging has become essential for the diagnosis and management of diseases, providing a range of techniques for obtaining images of internal organs and tissues of the human body. Advances in these imaging techniques have been rapid, leading to a concomitant increase in the use of these techniques for the diagnosis and monitoring of a range of diseases in both adults and children. Healthcare professionals increasingly rely on medical imaging to identify acute diseases, guide planning and treatment during surgical procedures, and monitor the progress of treatment. In particular, imaging plays a critical role in determining the effectiveness of treatment, and is required to determine the extent and spread of bone and soft tissue tumors prior to biopsy or surgical treatment. The use of medical imaging in a growing number of children, particularly in diagnostic radiology, has raised concerns in recent years that the corresponding exposure to ionizing radiation in children is high. Radiation exposure and risks in children underlie concerns about the effective dose to patients of known and potential carcinogenic effects. In general, these concerns center around two groups of techniques: computed tomography (CT) and interventional endoscopic examinations.